2020
DOI: 10.1371/journal.pone.0222253
|View full text |Cite
|
Sign up to set email alerts
|

Proprioceptive accuracy in Immersive Virtual Reality: A developmental perspective

Abstract: Proprioceptive development relies on a variety of sensory inputs, among which vision is hugely dominant. Focusing on the developmental trajectory underpinning the integration of vision and proprioception, the present research explores how this integration is involved in interactions with Immersive Virtual Reality (IVR) by examining how proprioceptive accuracy is affected by Age, Perception, and Environment. Individuals from 4 to 43 years old completed a self-turning task which asked them to manually return to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 65 publications
(72 reference statements)
4
26
1
Order By: Relevance
“…Setup. Materials and methods have been described in detail in our previous study with neurotypical children and adults [19]. The employed materials included a soundproof, 2x3 metre testing room with black interior walls where small white clouds were randomly fixed (see Figure 1), illumination, audio communication, and videotaping systems, and the HMD Oculus Gear VR 2016 (101 • FOV, 345 g weight, 60 Hz refresh rate) interfaced with a Samsung Galaxy S7 (152 g weight) providing IVR simulations (360 • pictures) of the testing room.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Setup. Materials and methods have been described in detail in our previous study with neurotypical children and adults [19]. The employed materials included a soundproof, 2x3 metre testing room with black interior walls where small white clouds were randomly fixed (see Figure 1), illumination, audio communication, and videotaping systems, and the HMD Oculus Gear VR 2016 (101 • FOV, 345 g weight, 60 Hz refresh rate) interfaced with a Samsung Galaxy S7 (152 g weight) providing IVR simulations (360 • pictures) of the testing room.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the broad research and intervention potential offered by HMDs, they have unique features that lead to sensorimotor interactions that do not constitute an exact corollary for real-world experience. Valori and colleagues [19] found that self-motion performance worsened in IVR conditions with vision available relative to the same conditions in reality and indeed, the way that HMDs deliver visual information has essentially unknown effects on movement and its perception [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are specific unique roles associated with each sensory source (i.e., somatosensory, visual, vestibular) that cannot be compensated fully with each other [14,15]. The environment is experienced through sensory systems: exteroception (e.g., sight, Proprioception and Clinical Correlation DOI: http://dx.doi.org/10.5772/intechopen.95866 hearing, touch), interoception (e.g., arousal, pain, visceral sensations, muscular sensations), and proprioception (e.g., sense of position, motion, and force), which all required for successful motor control [16,17]. During a task-oriented activity, motor adaptation, defined as a process of modifying the movement based on error feedback [18], skills are needed to cope with the changes occurring in the external and internal environment [2].…”
Section: Proprioception and Motor Controlmentioning
confidence: 99%
“…Researchers on the other hand, remain in full control and can track participants’ behaviour in great detail with advanced sensors. Consequently, VR has increasingly been used to study spatial navigation 1 , social interaction 2 and multisensory integration 3 . It has also been used in therapeutic settings such as stroke rehabilitation 4 , pain therapy 5 or phobia treatment 6 .…”
Section: Introductionmentioning
confidence: 99%